Mamíferos de la Selva Zoque, México: riqueza, uso y conservación - Lira-Torres, Iván (2012)
Mammals of Zoque Forest, Mexico: richness, use and conservation. Zoque Forest is one of the richest and threatened regions in Southeastern Mexico, and for which few studies on mammal biology and use are available. Here we analyzed the conservation status of mammalian species according to Mexican and international laws, with an updated checklist of mammals in this forest, and some information on their use by some rural communities. Basic information was obtained from national and international collections and publications. A total of 42 fieldtrips, that followed conventional techniques, were conducted from 2003 through 2010, and some questionnaires to local hunters were applied. The mammalian fauna found in the area was composed of 149 species belonging to 99 genera and 30 families; these results support that the Zoque Forest is the richest in the number of mammalian species in Mexico. A total of 35 species were considered at risk by the Mexican National Law NOM-059-SEMARNAT-2010, and 21 species were found to be registered in the IUCN Red List or in CITES. Of the 40 species included in any of the lists, only the Baird’s tapir, jaguar and white-lipped pec- cary were included in all three lists and 14 species were shared by the two of them. The main uses of mammals in order of importance are: 1) bushmeat, 2) pets, 3) skins, and 4) traditional medicine. Subsistence hunting and trade are unofficially allowed for farmers in this area. As for now, the region has healthy populations of a large number of mammals even though they have been used by local residents. However, since a considerable number of these species are listed under some criterion of threat, local authorities are called for more control.